A COMPARATIVE ANALYSIS OF PILLAR DESIGN METHODS AND ITS APPLICATION TO MARBLE MINES - González-Nicieza C.; Álvarez-Fernández M.I.; Menéndez-Díaz A.; Álvarez-Vigil A.E. (My University, 2006)
The methods for designing pillars in underground mines are fundamentally based on empirical formulae that do not take into account the quality of the rock mass as an input parameter. This makes them difficult to apply in other types of ground that are different to those used to establish each empirical formula. To avoid this inconvenience, the present paper examines existing empirical formulae to then propose a modification of these formulae adjusting the resistance of the pillars on the basis of the RMR (Bieniawski’s Rock Mass Rating). The compression safety factor of the pillars is analyzed for each modified formula and a study is carried out of shear failure if planes of weakness exist in the pillars. Finally, the safety factors of the pillars in a marble mine situated in Alicante (Southern Spain) were calculated in order to validate the new formulae. From the results obtained, it is concluded that this new formulation determines the safety factor of pillars of the mine with greater reliability, provided that the pillars are isolated. At the same time, the introduction of the RMR in the formulae results in a better fit of the strength of each pillar to the characteristics of the rock mass.
Keywords: PILLAR STRENGTH; FAILURE CRITERIA; INTACT ROCK; ROCK MASS; RMR.